PRESIDENTIAL GOVERNMENT SYSTEM STRENGTHENING THROUGH A PARTY SYSTEM SIMPLIFICATION (A COMPARISON BETWEEN THE INDONESIAN PARTY SYSTEM AND THE UNITED STATES PARTY SYSTEM) - Paramesthi Fajar, Ni Made Anggia (UNTAG Law Review, 2023)
Presidential system refers to a system of government in which the executive is not accountable to the legislature. The consequence of such as system is that the executive and legislature do not influence each other and are not influenced by each other. The basis of power of the executive is back to the people as the ultimate power holder. Hence, in accordance with the amendments to the 1945 Constitution of the Republic of Indonesia, the president is the head of state as well as the head of government assisted by a representative who is directly elected by the people. The people determine the election of a president and vice president and determine the (re-)election of a president and vice president for a second term. In practice, however, the implementation of this system of government is not in accordance with what has been mandated by the constitution